Prevalence of Cardiovascular Risk Factors among Young Adults (18–25 Years) in Mozambique - Isa Silva; Albertino Damasceno; Filipa Fontes; Natália Araújo; António Prista; Neusa Jessen; Patrícia Padrão; Carla Silva-Matos; Nuno Lunet (Journal of Cardiovascular Development and Disease, 2023)
The life course development of cardiovascular diseases (CVDs) and the undergoing epidemiological transition in Mozambique highlight the importance of monitoring the cardiovascular risk profile in young adults. Therefore, this study aims to estimate the prevalence of CVD risk factors in a population aged 18–25 years living in Mozambique. A total of 776 young adults from a nationally representative sample were evaluated in 2014/2015 following the World Health Organization’s STEPwise approach to chronic disease risk factor surveillance. Current smoking was the most prevalent among rural men (10.8%, 95%CI: 6.3–17.8), and drinking was most prevalent among urban men (38.6%, 95%CI: 29.3–48.8). The proportion of young adults not engaging in at least 75 min of vigorous physical activity per week ranged between 14.5% in rural men and 61.6% in urban women. The prevalence of being overweight/obese and hypertension were highest among urban women (21.6%, 95%CI: 14.7–30.6) and urban men (25.2%, 95%CI: 15.9–37.6), respectively. Education >8 years (vs. none) was independently associated with lower odds of being a current smoker, and increased monthly household income was associated with increased odds of low levels of physical activity. This study shows that important CVD risk factors are already common in the young adult population of Mozambique.